2003
DOI: 10.1126/science.1079204
|View full text |Cite
|
Sign up to set email alerts
|

Direct Fabrication of Large Micropatterned Single Crystals

Abstract: Micropatterning of single crystals for technological applications is a complex, multistep process. Nature provides alternative fabrication strategies, when crystals with exquisite micro-ornamentation directly develop within preorganized frameworks. We report a bio-inspired approach to growing large micropatterned single crystals. Micropatterned templates organically modified to induce the formation of metastable amorphous calcium carbonate were imprinted with calcite nucleation sites. The template-directed dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
537
0
17

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 526 publications
(567 citation statements)
references
References 28 publications
13
537
0
17
Order By: Relevance
“…The secondary nucleation mechanism by which crystallinity propagates in the sea urchin tooth is different from that produced in the laboratory by Aizenberg et al 17 In that study, Aizenberg et al generated a twodimensional ACC film deposited on a micropatterned substrate and converted it to calcite starting from a single nucleation site. This synthetic system is water-rich, and the crystallization mechanism involves dissolution and mass transport.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The secondary nucleation mechanism by which crystallinity propagates in the sea urchin tooth is different from that produced in the laboratory by Aizenberg et al 17 In that study, Aizenberg et al generated a twodimensional ACC film deposited on a micropatterned substrate and converted it to calcite starting from a single nucleation site. This synthetic system is water-rich, and the crystallization mechanism involves dissolution and mass transport.…”
Section: Discussionmentioning
confidence: 87%
“…15 Or, does an amorphous precursor phase form first and crystallinity propagate though it subsequently? 16,17 Ma et al observed that the fibers, and possibly the plates, are initially composed of amorphous calcium carbonate (ACC). 8 The present study reveals for the first time that the forming sea urchin tooth contains not one but two amorphous precursor minerals.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the dehydration of calcium carbonate was accelerated in porous templates because those pores functioned as pathways for the water exclusion and the dehydration. 7 The pores of the peptide assemblies capping nanoparticles could also provide the dehydration pathway promoting the β-Ga 2 O 3 growth in the cavities. Another potential factor to contribute the β-Ga 2 O 3 crystallization in the peptide assembly is the high surface tension built in the nanoscale peptide cavities.…”
Section: Resultsmentioning
confidence: 99%
“…The thin-walled (approximately 30 nm thick), interconnected silicate network in these coassembled composite films inhibits the formation/propagation of cracks for film thicknesses up to approximately 5 μm. Whereas the detailed mechanism of this unique crack-free growth is being currently investigated, we propose that the process might be similar to the formation of large single crystals of calcite patterned at the micron scale (51,52). In the latter case, the transformation of the amorphous CaCO 3 film into a defect-free, porous calcite crystal is facilitated by the micropatterned substrate that not only determines the pattern of porosity of the final single crystal, but also provides interfacial sites for stress and impurity release during the amorphous-to-crystalline transition.…”
Section: Resultsmentioning
confidence: 99%